PRAISE, COMPLIMENT AND FLATTERY AS MEANS OF REALIZATION OF INTIMATE COMMUNICATION STRATEGY - Н. А. Бігунова (Записки з романо-германської філології, 2020)
The article reports on the functioning of utterances of praise, compliment and flattery as tactics realizing intimate communication strategy. Positive evaluative utterances of praise, compliment and flattery have been differentiated according to the object and theme of evaluation. The linguistic status and pragmatic peculiarities of intimate communication strategy as a positive politeness strategy have been discussed. The material under analysis is represented by 1,500 contexts of positive evaluation taken by continuous sampling from English fiction. It has been established that intentions of the addressers of positive evaluation are not limited by a desire to express their positive evaluative opinion on the object and create a positive emotive mood, but they are also characterized by a wish to regulate the addressee’s behaviour, to create a contact or a good relationship with them, to manipulate them, to keep to a communication ritual, etc. Besides, positive evaluative utterances can be used to realize the strategies of positive and negative politeness. Intimate communication strategy has been classified as a strategy of positive politeness, as well as such strategies as contactestablishing strategy and the strategy of saving the addressee’s face. Intimate communication strategy, also known as the tactics of solidarity, or the tactics of belonging to the same group, accentuates community of world view, interests and aspirations of interlocutors. As the analysis of the investigated data shows, it is positive evaluative utterances that help to demonstrate solidarity with the interlocutor and to create “the language of a small society”, the marker of a specific language, opposed to the language of other societies. A positively charged communicant relies on positive evaluation of a certain object as a means of creating a certain communication mode, intimate, trustworthy, friendly. In this way interlocutors are connected into a certain community, exchanging significant for both of them feelings and experiences. The analysis of the data brings us near the position that the taken strategy is most commonly used by the addressers of compliments.